KEBIJAKAN FISKAL DAN MONETER DALAM PERSPEKTIF ISLAM - Gustia Gustia; Jumaini S; An Ras Try Astuti (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2024)
Fiscal and monetary policy are the main instruments used by the government to manage a country's economy. Fiscal policy in Islam focuses on managing state revenues and expenditures in accordance with the principles of justice and social welfare. State revenues in the form of Zakat, Jizyah, and Kharaj are used to fund expenditures that support equitable economic and social development, such as equitable distribution of wealth and fulfillment of basic needs of the community. Monetary policy in an Islamic perspective is a practice to avoid usury (interest) and encourage the use of financial instruments based on the principle of profit sharing and real trade. The central bank in the Islamic economic system functions to ensure monetary stability through controlling the amount of money supply and maintaining the value of the currency with a mechanism that does not contain elements of usury. These two policies must be carried out in synergy to achieve the objectives of sustainable economic development, price stability and fair distribution of wealth in accordance with sharia principles. The implementation of fiscal and monetary policies in accordance with Islamic teachings is expected to provide an economic system that prioritizes justice and is able to face global economic challenges while upholding Islamic values.